GERAKAN MEMASYARAKATKAN MAKAN IKAN (GEMARIKAN) DI SD NEGERI 4 KLATAKAN DUSUN PECARON, SITUBONDO, JAWA TIMUR - haini, naufara; Lestari, Dewi Putri; Sumsanto, Muhammad; Diamahesa, Wastu Ayu; Miranti, Sevia; Andriana, Ina Eka; Khofiatun, Fadliana; Ahyani, Dina; Yuastika, Windi; Shalehah, Atiatun (Jurnal Pengabdian Perikanan Indonesia, 2025)
Pecaron Hamlet, Klatakan Village, is located in Kendit District, Situbondo Regency, East Java, and is one of the areas rich in natural resource potential, including the fisheries and agricultural sectors. The capture fisheries and aquaculture sectors are advantages, however, there are still shortcomings in utilizing existing potential, then there is still a lack of interest from the community, especially children, to consume processed fish which is feared to have an impact on the fulfillment of children's nutrition which is less than optimal. Therefore, in an effort to increase the existing fisheries potential and the interest of the community in all circles, especially early childhood, adolescents to adults to start liking or being fond of consuming fish, especially in the Pecaron hamlet environment, Situbondo, East Java, with the KKN Merdeka Belajar Kampus Merdeka Universitas Mataram activity, it is hoped that it will be able to achieve this through the implementation of the Fish Eating Movement Socialization program and other programs that have been agreed upon with the village. The interest in eating fish of children at SDN 4 Klatakan is quite high, but there are indeed some students who do not like it because of the lack of creative processed fishery products consumed, this can be seen based on the enthusiasm shown when given nuggets made from 100% fish from participants who like it, so in increasing GEMARIKAN this can be done by all parties by continuing to develop creative processed fish that are attractive to children, one of which is fish nuggets.